Noninactivating voltage-gated sodium channels in severe myoclonic epilepsy of infancy - Rhodes, Thomas H. (National Academy of Sciences, 2004)
Mutations in SCN1A, the gene encoding the brain voltage-gated sodium channel α(1) subunit (Na(V)1.1), are associated with at least two forms of epilepsy, generalized epilepsy with febrile seizures plus and severe myoclonic epilepsy of infancy (SMEI). We examined the functional properties of five SMEI mutations by using whole-cell patch-clamp analysis of heterologously expressed recombinant human SCN1A. Two mutations (F902C and G1674R) rendered SCN1A channels nonfunctional, and a third allele (G1749E) exhibited minimal functional alterations. However, two mutations within or near the S4 segment of the fourth repeat domain (R1648C and F1661S) conferred significant impairments in fast inactivation, including persistent, noninactivating channel activity resembling the pattern of channel dysfunction observed for alleles associated with generalized epilepsy with febrile seizures plus. Our data provide evidence for a range of SCN1A functional abnormalities in SMEI, including gain-of-function defects that were not anticipated in this disorder. Our results further indicate that a complex relationship exists between phenotype and aberrant sodium channel function in these inherited epilepsies.